Pre-combustion carbon dioxide capture materials - Wang, Qiang (Inorganic materials series (Royal Society of Chemistry (Great Britain)) ;, 2018)
An introduction to the different inorganic adsorbents/sorbents used in pre-combustion carbon dioxide capture.